Effectiveness and safety of the PlasmaJet® Device in advanced stage ovarian carcinoma: a systematic review - Gatske M. Nieuwenhuyzen-de Boer; Jacoba van der Kooy; Heleen J. van Beekhuizen (BMC, 2019)
Abstract About 80 % of all women affected by ovarian cancer present with advanced stage disease at the time of diagnosis. Achieving complete cytoreduction is complicated when many small tumor spots are found. Yet, complete cytoreduction is the most important determinant of survival. Application of a thermal plasma energy device to standard surgical instruments may help achieve complete cytoreduction. The 'PlasmaJet® Device' (Plasma Surgical, Inc., Roswell, GA, USA) is an electrically neutral device which emits a high-energy jet of argon plasma for direct tissue effects. We performed a literature review to investigate whether the use of the 'PlasmaJet® Device' in surgery of advanced stage ovarian carcinoma (FIGO IIIB-IV) is effective and safe. The primary outcome was the proportion of complete cytoreductions. The secondary outcomes were: complication rate, proportion of colostomies applied, histological findings, disease-free survival and overall survival. Five case series or reports were found, including a total of 77 patients with FIGO stage IIIC-IV ovarian cancer in whom the PlasmaJet® device was used for primary or interval debulking. Complete cytoreduction was obtained in 79% of the patients. Apart from one pneumothorax after extensive surgery, but no harm or additional complications related to the use of the PlasmaJet® Device were reported. Data on disease-free survival or overall survival were not reported. These findings suggest that the PlasmaJet® Device is an efficient and safe innovative surgical device for debulking surgery with encouraging results. We have proposed an RCT in which we will compare feasibility, safety and effectiveness aspects of the use of the PlasmaJet® versus conventional electrosurgery in advanced stage epithelial ovarian cancer (FIGO IIIB-IV).